11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10)

Simple and best practice solution for 11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10) equation:


Simplifying
11 + 9(8z + 16) = -6z + 5 + -19(4z + -9) + 11(5z + -10)

Reorder the terms:
11 + 9(16 + 8z) = -6z + 5 + -19(4z + -9) + 11(5z + -10)
11 + (16 * 9 + 8z * 9) = -6z + 5 + -19(4z + -9) + 11(5z + -10)
11 + (144 + 72z) = -6z + 5 + -19(4z + -9) + 11(5z + -10)

Combine like terms: 11 + 144 = 155
155 + 72z = -6z + 5 + -19(4z + -9) + 11(5z + -10)

Reorder the terms:
155 + 72z = -6z + 5 + -19(-9 + 4z) + 11(5z + -10)
155 + 72z = -6z + 5 + (-9 * -19 + 4z * -19) + 11(5z + -10)
155 + 72z = -6z + 5 + (171 + -76z) + 11(5z + -10)

Reorder the terms:
155 + 72z = -6z + 5 + 171 + -76z + 11(-10 + 5z)
155 + 72z = -6z + 5 + 171 + -76z + (-10 * 11 + 5z * 11)
155 + 72z = -6z + 5 + 171 + -76z + (-110 + 55z)

Reorder the terms:
155 + 72z = 5 + 171 + -110 + -6z + -76z + 55z

Combine like terms: 5 + 171 = 176
155 + 72z = 176 + -110 + -6z + -76z + 55z

Combine like terms: 176 + -110 = 66
155 + 72z = 66 + -6z + -76z + 55z

Combine like terms: -6z + -76z = -82z
155 + 72z = 66 + -82z + 55z

Combine like terms: -82z + 55z = -27z
155 + 72z = 66 + -27z

Solving
155 + 72z = 66 + -27z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '27z' to each side of the equation.
155 + 72z + 27z = 66 + -27z + 27z

Combine like terms: 72z + 27z = 99z
155 + 99z = 66 + -27z + 27z

Combine like terms: -27z + 27z = 0
155 + 99z = 66 + 0
155 + 99z = 66

Add '-155' to each side of the equation.
155 + -155 + 99z = 66 + -155

Combine like terms: 155 + -155 = 0
0 + 99z = 66 + -155
99z = 66 + -155

Combine like terms: 66 + -155 = -89
99z = -89

Divide each side by '99'.
z = -0.898989899

Simplifying
z = -0.898989899

See similar equations:

| 4/(z+2)-1/(3z+6)=11/9 | | y^4+y^3+2y^2=0 | | 6x+2=5x+6 | | 2x-3/6+3x-2/4+5x+6/12=4 | | 75=3(10t-3)6t | | 2+5x=7+4x | | -x-4=-2x | | -18(13y+12)=-17+16(13y+8)-15(9y+17) | | 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x | | -14+28x+26x=16x-12+8x | | -14-28x+26x=16x-12+8x | | 91=7(1+2x) | | 2x+4=39-5x | | 24z+27+13z=25-9z-5z | | 3=16+(x+1) | | -x+4=-2x+6 | | 9-4y=-11-6y |

Equations solver categories